Analysis of Quranic Learning Methods at Rumah Tahsin and Tahfizh (RTT) Al Birru Bolon Branch - Khalid Abdurrahman Sulis; Nurul Latifatul Inayati (Tadrib: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the Qur'anic learning methods implemented at Rumah Tahsin dan Tahfizh (RTT) Al Birru, Bolon Branch, with a focus on the application of talaqqi and talqin methods. Using a qualitative descriptive approach, data were collected through interviews, observation, and documentation involving instructors and learners. The study investigates how these methods shape students' learning experiences and memorization outcomes. Findings indicate that the implementation of talaqqi and talqin fosters direct interaction between teachers and learners, ensuring accurate pronunciation and more profound comprehension of Qur'anic verses. In addition, structured repetition and individualized correction contribute to more effective tahsin and tahfizh processes. This study contributes to the academic discourse by presenting empirical evidence of the continued relevance of classical Qur'anic pedagogy in modern non-formal education settings. The results highlight the potential of integrating traditional methods with contemporary learning management to enhance engagement and retention. It is recommended that further research explore comparative effectiveness across different institutions, as well as the integration of digital tools to support classical approaches. The study affirms that contextually adapted traditional methods remain effective in producing meaningful Qur’anic literacy among learners.